Students’ Perception on Learning Technical Vocabularies through Vocabulary Self-Collection Strategy - Difa Viola; Elih Sutisna Yanto; Mobit Mobit (Journal of Languages and Language Teaching, 2020)
The objective of this research was to investigate vocational students’ perception on learning technical vocabularies through Vocabulary Self-Collection Strategy. This research provides two research questions, 1) In what ways Vocabulary Self-Collection Strategy facilitate students in learning technical vocabulary? 2) What are the constraints of the students in the learning of technical vocabulary using Vocabulary Self-Collection Strategy? This research was using qualitative methodology and virtual classroom action research as a research design due to the pandemic of Covid-19. The participants of this research are grade 10th students of audio-video engineering from one of vocational high school in Karawang, West Java, Indonesia. A chosen audio-video engineering journal was distributed in order for the students to explored and selected new important words and added the information they got from it to vocabulary self-collection strategy (VSS) chart. And also semi-structured interviews have completed to know their perception on vocabulary self-collection strategy during learning technical vocabulary using VSS (selecting and nominating new words). The result of this study showed that vocabulary self-collection strategy had positive impacts to students’ vocabulary size, their ability to comprehend text and the constraints that the students had during the VSS process.